Shared Psychotic Disorder Associated With Bipolar Disorder in the Primary Case in the Context of Opioid Misuse. Issue 3 (5th May 2022) - Livne, Ofir; Sinai, Omri; Lev-Ran, Shaul
Abstract : Bipolar disorder (BD) is a serious chronic mood disorder associated with high rates of co-occurring substance use disorders. Shared psychotic disorder (SPD) is a rare clinical phenomenon and has been reported in only a few cases of individuals diagnosed with BD. Furthermore, reports concerning SPD being induced by substance use or withdrawal are lacking. We report the case of a married couple endorsing simultaneous psychosis, a form of SPD. The primary case (the wife) had a diagnosis of BD, without any history of psychotic episodes before the current episode, while the secondary case (the husband) had a diagnosis of posttraumatic stress disorder. Both individuals were misusing prescribed synthetic opioids, and their psychosis was most likely induced by a withdrawal state. Cases of SPD involving patients with BD have rarely been reported. Considering the high rates of dual diagnoses among patients with BD, clinicians should be aware of the risk of substance-induced psychosis among these individuals and the manifestation of these psychotic episodes. This case report strengthens previous reports suggesting that SPD is a clinical entity that can occur not only in situations where the primary case involves an individual diagnosed with delusional disorder or schizophrenia, but that it may also occur when the primary case has a diagnosis of BD.